PENGEMBANGAN KARAKTER PANCASILA PADA MAHASISWA CALON KATEKIS DAN GURU AGAMA KATOLIK SEBAGAI UPAYA MEMINIMALISIR BUDAYA MENYONTEK - Rani, Nyifta Maha; Dewantara, Agustinus Wisnu (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2023)
This study aims to describe the importance of developing Pancasila’s character for prospective Catechist and Catholic Religious Teacher students to minimize the culture of cheating and at the same time to meet the needs of students, namely having superior character. This study uses a qualitative method with a purposive sampling technique, namely an informant selection technique using certain criteria. The data collection technique uses the interview method and in the data collection process, documentation is included as evidence of the implementation of the research. The results show that Pancasila's character is essential for students. One of them, Pancasila becomes a guideline in acting and becomes a noble value that must be preserved which will then become the identity of students. The challenges for students in appreciating the values of Pancasila are mostly coming from within the students themselves and various influences from outside the students themselves. Therefore, the results of the analysis show that Pancasila’s character development is needed for prospective Catechist and Catholic Religious Teacher students. This character development will be a solution to meet the needs of students in having superior character as provisions in their mission as Catechists and Catholic Religious Teachers.